Improving the sub-base materials at Al-Fao port in Basrah Governorate-South of Iraq by adding some synthetic polymers and cement - Al-Maliki, F.S.; Mahmood, R.A.; Jabir, M.A. (Mesopotamian Journal of Marine Sciences, 2021)
The improvement process by adding polymers and cement has been carried out to sub-base material used in the compaction processes, in order to observe their effects on the geotechnical properties of the sub-base such as compaction, unconfined compressive strength, shear strength, California bearing ratio and absorption ratio. It has been observed that there is a significant improvement in the geotechnical properties of the soil as the value of the maximum dry density increased from 2.144 to 2.220 g/cm3, while the value of the optimum moisture contents decreased from 6.3 to 5.2% with a percentage of 5 % of the first polymer (Polyvinyl Acetate & Polyol). It is also revealed that there is an increase in the value of the unconfined compressive strength after adding 5% of the first polymer and 5% cement to the sub-base sample, and then soaked in water for different periods of time, the result was 11550 kPa with a soaking period of 28 days. Also, the angle of the internal friction values increased in testing the direct shear strength from 35◦ to 45◦ by adding 5% of the first polymer, and cohesion occurrence among the particles of the material under the action of the polymer as a adhesive material, the value reached 200 kN/m2. The California bearing ratio increased from 49% to 64% by adding 5% of the first polymer, while the absorption ratio decreased considerably at the same ratio and material from 9.8% to 4.1%.